2014
DOI: 10.2151/sola.2014-010
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Difference between Meteorological Station and Nearby Farmland –Case Study for Kumagaya City in Japan–

Abstract: The seasonal (monthly) variation in temperature difference between a meteorological station in an urban-area and nearby farmland in Kumagaya City was examined over 2010−2012. Kumagaya, one of the hottest cities in Japan, has an urban area of about 5 × 5 km and is surrounded by farmland. The daily mean, maximum, and minimum temperatures (T mean , T max , and T min ) routinely observed at the meteorological station (urban site) were higher than at the nearby farmland site across all seasons. Differences in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
2
14
0
Order By: Relevance
“…However, local conditions at experimental stations can differ from those at AMeDAS stations depending on the surrounding land use. A recent study reported differences in air temperature of as much as 1℃ between an agricultural experimental station and a nearby weather station during the rice-growing season (Kuwagata et al, 2014). Selection of one or a few fixed experimental stations and their associated weather stations may result in a consistent bias in the parameters estimated, if there is a consistent bias in the weather station data.…”
Section: Discussionmentioning
confidence: 99%
“…However, local conditions at experimental stations can differ from those at AMeDAS stations depending on the surrounding land use. A recent study reported differences in air temperature of as much as 1℃ between an agricultural experimental station and a nearby weather station during the rice-growing season (Kuwagata et al, 2014). Selection of one or a few fixed experimental stations and their associated weather stations may result in a consistent bias in the parameters estimated, if there is a consistent bias in the weather station data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the temperature difference between the two sites during the wheat or barley growing season mid-November to early June was not as large. Other studies have also reported differences in the daytime temperature of over 1 C between urban areas and rice paddy fields Sakakibara, 1994;Sakakibara et al, 1996;Sakakibara and Morita, 2002;Wakiyama, 2007. Kuwagata et al 2014 suggested that the daytime temperature difference between the urban area and the rice paddy field may have been increased by greater heat loss due to evapotranspiration at the rice paddy field during the paddy rice growing season.…”
Section: Introductionmentioning
confidence: 94%
“…Agriculture is strongly influenced by meteorological conditions, and their variations in farmland areas are among the basic environmental factors that affect crop production. Although meteorological data measured at meteorological stations of the Japan Meteorological Agency JMA are commonly used in Japan for assessing both the impact of climate change on crop production and crop management practices Seino, 1993;Hasegawa et al, 2011;Ishigooka et al, 2011;Kuwagata et al, 2011;Fukuoka and Yoshimoto, 2012;Ohno et al, 2016 , many of these meteorological stations are in urban areas whereas relatively few are in farmland areas Nishimori et al, 2009;Murakami et al, 2011;Kuwagata et al, 2014 . Local land cover affects meteorological conditions at an observation site by changing the local-scale and microscale environment at the site Fujibe, 2012;Kondo, 2012Kondo, , 2016 In urban areas, meteorological conditions are commonly influenced by the urban heat island effect, and the land cover grass, bare soil, asphalt, etc. adjacent to an observation site also influences micrometeorological conditions at the site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations